Adaptation of fear of missing out scale (FoMOs): Turkish version validity and reliability study - Can, Gurhan; Satici, Seydi Ahmet (SPRINGER INTERNATIONAL PUBLISHING AG, 2019)
BackgroundThe aim of this study is to examine psychometric properties of the Turkish version of the fear of missing out scale (FoMOs) on three different study groups.MethodWe conducted the construct validity of the Turkish FoMOs with confirmatory factor analysis, measurement invariance (study I; n=354), and concurrent validity (study II; n=371). We also evaluated the reliability of the Turkish FoMOs (study III; n=61) using test-retest and Cronbach alpha reliability.ResultsIn study I, the confirmatory factor analysis revealed that the one-dimensional structure of the Turkish version of the FoMOs was verified. The results of measurement analysis depending on the sample of study I demonstrated that configural and metric invariances were established across Facebook and other social media users. The Cronbach alpha values calculated from the samples of study I (=.79) and study II (=.78) indicated that internal consistency of the scale was at the acceptable level. Lastly, test-retest reliability of the scale was found as .86 from the study III.ConclusionOverall findings indicated that the psychometric properties of the Turkish version of FoMO scale were satisfactory to measure the FoMO in a wide range of ages in the Turkish context.
Keywords: Fearing of missing out; Social media; Psychometric properties; Scale adaptation